2020
DOI: 10.2139/ssrn.3738213
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of ICTs and Digitalization on Productivity and Labor Share: Evidence from French firms

Abstract: Taking advantage of an original firm-level survey carried out by the Banque de France, we empirically investigate how the employment of ICT specialists (in-house and external) and the use of digital technologies (cloud and big data) have an impact on firm productivity and labor share. Our analysis relies on the survey responses in 2018 of 1,065 French firms belonging to the manufacturing sector and with at least 20 employees. To tackle potential endogeneity issues, we adopt an instrumental variable approach as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 19 publications
0
8
2
Order By: Relevance
“…Studies have found that the use of digital technology by various companies is associated with higher labour productivity and firm growth (Clarke et al, 2015). Cette et al (2021) investigated impact of information communication technology (ICT) and digitalization on total factor and labour productivity. Their find out that the employment of ICT specialists and the use of digital technologies improves firms labour productivity by 23% and its total factor productivity by about 17%.…”
Section: Measuring Digitalization Impact On Labor Productivitymentioning
confidence: 99%
See 4 more Smart Citations
“…Studies have found that the use of digital technology by various companies is associated with higher labour productivity and firm growth (Clarke et al, 2015). Cette et al (2021) investigated impact of information communication technology (ICT) and digitalization on total factor and labour productivity. Their find out that the employment of ICT specialists and the use of digital technologies improves firms labour productivity by 23% and its total factor productivity by about 17%.…”
Section: Measuring Digitalization Impact On Labor Productivitymentioning
confidence: 99%
“…In their study they used Brazilian industry data of year 2016 of 27 industrial sector and 2225 companies. Cette et al (2021) relied on analysis of survey in 2018 of 1065 French firms belonging to manufacturing sector with at least 20 employees. So, all the studies before on digitalization impact been done for limited target year and specific country.…”
Section: Limitations Of Available Studies and Datamentioning
confidence: 99%
See 3 more Smart Citations